2021
DOI: 10.3390/land10080817
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Recent (1985–2014) Patterns of Land Abandonment and Environmental Factors in the Establishment and Growth of Secondary Forests in the Iberian Peninsula

Abstract: Farmland abandonment has been a widespread land-use change in the Iberian Peninsula since the second half of the 20th century, leading to the establishment of secondary forests across the region. In this study, we aimed to address changes in the recent (1985–2014) emergence patterns of these forests and examine how environmental factors affected their growth by considering differences in leaf-habit types. We used a combination of Landsat-derived land-cover maps and aboveground biomass (AGB) maps from the Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
(152 reference statements)
0
4
0
1
Order By: Relevance
“…Our results showed that the main topoclimatic determinant of crop abandonment to new BDF was precipitation, mainly in the case of rainfed crops with an increasing positive tendency. In some studies, this variable was initially removed due to the correlation with other drivers [30,64], whereas in others, it appeared as the main one [21,66]. Other topoclimatic drivers obtained from our analysis were temperature and slope, with a negative (except for the Thermomediterranean region) and a positive gradient, respectively.…”
Section: Drivers Of Forestation From Croplandsmentioning
confidence: 91%
See 2 more Smart Citations
“…Our results showed that the main topoclimatic determinant of crop abandonment to new BDF was precipitation, mainly in the case of rainfed crops with an increasing positive tendency. In some studies, this variable was initially removed due to the correlation with other drivers [30,64], whereas in others, it appeared as the main one [21,66]. Other topoclimatic drivers obtained from our analysis were temperature and slope, with a negative (except for the Thermomediterranean region) and a positive gradient, respectively.…”
Section: Drivers Of Forestation From Croplandsmentioning
confidence: 91%
“…Studies quite often evaluate the drivers involved in LC dynamics focusing on a specific issue or complex phenomenon to be analyzed, unifying several categories from LC maps into a unique "label", i.e., forest regrowth, deforestation, and cropland abandonment, which constitutes the phenomenon as a target for analysis in research works [19,21,30,33]. The study also benefited from investigating NF appearance, disaggregated into three forest types, focusing on six main source categories for the sake of understanding the specific drivers involved.…”
Section: Driving Forces Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…factores que condicionan la disponibilidad de agua y determinan diferentes trayectorias o transiciones forestales, en las que unas comunidades forestales son beneficiadas frente a otras que resultan perjudicadas (Delgado-Artés et al, 2022;José Vidal-Macua et al, 2017). La matorralización y revegetación con bosques secundarios evidencia una adaptación de las comunidades mejor adaptadas a la sequía (Palmero-iniesta et al, 2021), parámetro que está experimentando una tendencia positiva si consideramos los incrementos de temperatura y evapotranspiración en el sur de la península ibérica (Páscoa et al, 2021;Tomas-Burguera et al, 2021). En este nuevo contexto socioecológico y ambiental, el impacto de los incendios forestales está cobrando una mayor importancia sobre la dinámica de la vegetación en la región mediterránea (Resco de Dios et al, 2006).…”
Section: Los Límites Del Reverdecimientounclassified
“…Besides the recent extreme weather events, the rapid fuels buildup since the 1960s is also a primary driver behind catastrophic wildfires in Portugal and the European Mediterranean areas. The highly fragmented cultural landscapes evolved into a dense forest continuum that resulted from rural population exodus, extensive afforestation efforts to grow commercial softwood, farmland abandonment, and livestock confinement [12][13][14][15][16]. The suburban sprawl around city centers expanded into the surrounding agricultural plains [17,18], and rapid-growing conifer species and shrublands invaded abandoned olive groves, vineyards, small arable land parcels, and grasslands [19].…”
Section: Introductionmentioning
confidence: 99%